FORMATION OF A CUSTOMER-ORIENTED DEVELOPMENT STRATEGY FOR ORGANIC OPERATORS (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The study analysed various scientific approaches to the problem of forming a customer-oriented strategy for enterprise development. Thus, the study has identified several key approaches that contribute to the creation of an effective customer orientation strategy.  The stages of formation of a customer-oriented development strategy for operators in the organic market. The main components of the customer-oriented development strategy of operators in the organic market are identified in terms of key aspects: development and innovation in the product range; introduction of effective marketing communication; improvement of service quality; development of partnerships.
Keywords: customer orientation; marketing approaches; organic products; sustainable development; social responsibility; customer experience